COVID-19 and leisure: Costa Rica’s case - Fumero-Vargas, Patricia (2022)
Leisure and recreation during the COVID-19 pandemic in Costa Rica is studied to analyze routines and recreation performed by the Costa Rican population. It is based on a non-probabilistic convenience sampling answered by 423 people over 18 years of age. In the study, the population is characterized by age, gender, educational level, profession/occupation, and income. The relationship between the participants and their preferred type of entertainment, about sports and their motivation, as well as their hobbies, is established based on this data.